2017
DOI: 10.1177/0032321716667956
|View full text |Cite
|
Sign up to set email alerts
|

Legitimacy from Decision-Making Influence and Outcome Favourability: Results from General Population Survey Experiments

Abstract: Democracies are typically considered more legitimate than other types of regimes because they allow the citizens to participate in the policy decision-making process. Others argue that the policy output matters most, and citizen influence plays a lesser role. This study presents two survey experiments on the micro foundations of these two sources of political legitimacy, thus contributing to an emerging literature that experimentally investigates the effects of democratic procedures in small-scale settings. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 46 publications
6
78
2
Order By: Relevance
“…Our study thereby relates to an emerging strand of literature in political science that uses experimental approaches to investigate citizens' legitimacy beliefs and their assessment of various decision-making arrangements (see Tyler 1994;Esaiasson et al 2012;Arnesen 2017). Since we are interested in the relationship between different attributes of governance arrangements that drive citizens' evaluations, an experimental design that allows a random variation of these attributes is the best strategy for studying how these variations affect citizens' legitimacy beliefs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study thereby relates to an emerging strand of literature in political science that uses experimental approaches to investigate citizens' legitimacy beliefs and their assessment of various decision-making arrangements (see Tyler 1994;Esaiasson et al 2012;Arnesen 2017). Since we are interested in the relationship between different attributes of governance arrangements that drive citizens' evaluations, an experimental design that allows a random variation of these attributes is the best strategy for studying how these variations affect citizens' legitimacy beliefs.…”
Section: Methodsmentioning
confidence: 99%
“…Previous experimental studies on similar topics focus on how various modes of decision making in small-scale settings affect individual assessments of procedural fairness (Tyler 1994;Esaiasson et al 2016b), or decision acceptability (Esaiasson et al 2016a;Arnesen 2017). Previous experimental studies on similar topics focus on how various modes of decision making in small-scale settings affect individual assessments of procedural fairness (Tyler 1994;Esaiasson et al 2016b), or decision acceptability (Esaiasson et al 2016a;Arnesen 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that outcome favorability is an important factor for the acceptance of a decision (Arnesen, 2017). Citizens are likely to be concerned with the outcome of the decision, and we thus expect that the legitimacy is higher when the decision is in line with the respondent's preference.…”
Section: Expectationsmentioning
confidence: 99%